Clinical Approaches to Cultural Diversity in Mental Health Care and Specificities of French Transcultural Consultations: A Scoping Review - Carballeira Carrera, Laura; Lévesque-Daniel, Sarah; Radjack, Rahmeth; Moro, Marie Rose; Lachal, Jonathan (Frontiers in Psychiatry, 2020)
Background: Cultural context substantially affects the experience and clinical expression of psychiatric diseases, while cultural factors limit both access to and effectiveness of care, especially for migrant families requiring specific types of services. We conducted a scoping review on psychiatric services adapted to cultural diversity, to compare these models of care to the French Transcultural Psychotherapy model. Methods: Systematic electronic search of databases (PubMed and PsycINFO), manual search of archives of journals dealing with transcultural psychiatry, and consultations with international experts, to identify all papers describing clinical models devoted to psychiatric care for migrants, published between January 1990 and October 2018. Narrative synthesis of the included articles. Results: The study included 29 papers. The specificities of psychiatric services for migrant families are linked to the host country's migration patterns and citizenship model. In English-speaking countries, specialized services for ethnic minorities offer ethnic matching of the therapist and patient. In Canada, indirect transcultural consultation services have existed since the late 1990s. Australia emphasizes the networking of consultation services and professional training in cultural competence, while the Nordic countries (Sweden, Finland, Norway, and Denmark) focus management on trauma. In France, psychotherapy services, with flexible numbers of therapists involved according to the situation, have existed since 1990. Discussion: Most initiatives place emphasis on training and supervision, in an indirect approach not specifically focused on the patient, or offer cultural matching of patient and therapist. The French transcultural approach, on the contrary, makes the family's culture and its cultural diversity an integral part of the therapy process.